Material for adsorbing biogenic substance

JP2025036356APending Publication Date: 2025-03-14TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024148086
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-30
Publication Date
2025-03-14

Smart Images

  • Figure 2025036356000001
    Figure 2025036356000001
  • Figure 2025036356000002
    Figure 2025036356000002
Patent Text Reader

Abstract

To provide a material for adsorbing a biogenic substance, which exhibits both high adsorption ability for a biogenic substance, particularly cytokine, and low adsorption ability for heparin.SOLUTION: A material for adsorbing a biogenic substance includes: a water-insoluble material comprising a substrate including a polymer having an aromatic ring as a repeating unit, a sulfonic acid group fixed onto the substrate, and a cross-linking structure for cross-linking the polymer, where the content of the sulfonic acid group is 0.2-2.0 mmol per 1 g of the water-insoluble material, and the water content of the water-insoluble material is 60% or more and less than 100%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biological component-adsorbing material. [Background technology]

[0002] In recent years, technologies related to blood purification therapy that adsorb and remove biological components such as cytokines and white blood cells have been developed for the purpose of treating inflammatory diseases, suppressing the immune system before and after transplantation, and suppressing side effects such as fever and infection caused by blood products. Among them, technologies have been developed to adsorb and remove cytokines, especially interleukin 6 and interleukin 8, which are biomarkers for inflammatory diseases.

[0003] Materials that have cross-linked structures and sulfonic acid groups fixed to the substrate are physically stable and do not easily produce eluates, and the negative charge of the sulfonic acid groups makes it possible to control electrostatic interactions. Taking advantage of these properties, a large number of materials have been developed for adsorbing biological components, including cytokines.

[0004] For example, Patent Document 1 discloses a carrier for adsorbing biological components, in which a functional group having an acidic functional group selected from the group consisting of sulfate, sulfite and sulfonic acid groups and an amino group is introduced onto the surface of a water-insoluble carrier made of fibers or particles, the fiber diameter of the fibers or the particle diameter of the particles is 0.5 to 20 μm, and the negative charge amount of the water-insoluble carrier is 1.5×10-5 to 1.5×10-3 eq / g. It is disclosed that the feature of the adsorption carrier is that by introducing a zwitterionic functional group having both an acidic functional group and an amino group, which is a basic functional group, it is possible to simultaneously remove cytokines and three types of leukocyte components.

[0005] Patent Document 2 discloses a fiber for adsorbing proteins, which has a water absorption rate of 1 to 50%, and contains a polymer in which aromatic hydrocarbons or derivatives thereof are used as repeating units, and part of the aromatic rings of the repeating units are crosslinked via a specific chemical structure. It is disclosed that the feature of the fiber for adsorption is that it is possible to exert cytokine adsorption ability and an effect of suppressing the generation of fine particles by controlling the water content.

[0006] Patent Document 3 discloses an adsorbent for tumor necrosis factor-α composed of a styrene-divinylbenzene copolymer having sulfonic acid groups, and discloses an ion exchange resin, Diaion HPK55, as an example. However, although it is disclosed that the ion exchange capacity corresponding to the content of sulfonic acid groups of Diaion HPK55 is about 1 meq / mL, the ion exchange capacity per dry weight is not disclosed. As described in Non-Patent Document 1, the Diaion HPK series is currently out of the market, and its successor is Diaion RCP160M. Non-Patent Document 2 discloses that the density (apparent density) of the ion exchange resin in the water-containing state of Diaion RCP160M is 740g / L, and the water content is 45-55%. In other words, the density of the ion exchange resin in the dry state of Diaion RCP160M is 333-407g / L. Assuming that the density of the dry ion exchange resin is the same for the DIAION HPK series and DIAION RCP160M, the ion exchange capacity per dry weight of DIAION RCP160M is estimated to be about 2.5 to 3.0 meq / g. As described in Non-Patent Document 1, the DIAION HPK series and DIAION RCP series are highly cross-linked highly porous ion exchange resins, and the water content includes not only the water contained in the resin but also the water in the macropores. In addition, it is disclosed that the standard cross-linked resin has a cross-linking degree of 8 wt% as the amount of divinylbenzene charged.

[0007] Patent Document 4 describes a blood supply device comprising a container having a blood inlet and a blood outlet, and a biocomponent adsorbing material filled in the container, the biocomponent adsorbing material being made of a woven or knitted fabric, the opening ratio of the woven or knitted fabric being 3% or more and less than 10%, and the filling density of the biocomponent adsorbing material being 0.30 g / cm. 3 More than 1.30g / cm 3 The value obtained by multiplying the opening ratio by the filling density is 1.1% g / cm or less. 3 More than 3.9% g / cm 3 A biocomponent adsorption column is disclosed in which the capacity is less than

[0008] In blood purification therapy, blood is drawn out of the body and comes into contact with foreign bodies. Among blood components, cellular components are activated and coagulated when they come into contact with foreign bodies. This causes blood to clot, so when blood is passed through a column filled with a biocomponent adsorption material, an anticoagulant is generally used to suppress the coagulation of cellular components. In particular, when a column filled with a biocomponent adsorption material is used for blood purification therapy, the column becomes clogged due to blood coagulation, making it impossible to perform treatment, so an anticoagulant must be constantly administered during blood purification therapy. There are several types of anticoagulants, such as heparin, nafamostat mesilate, and citric acid, but heparin is generally used preferably. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent No. 5929197 [Patent Document 2] International Publication No. 2016 / 043223 [Patent Document 3] Patent No. 3633978 [Patent Document 4] JP 2018-102659 A [Non-patent literature]

[0010] [Non-Patent Document 1] Mitsubishi Chemical Corporation, “DIAION MANUAL OF ION EXCHANGE RESINS AND SYSTHETIC ADSORBENTS 1 (Sixth Edition)”, March 2018, p3~22 [Non-Patent Document 2] Mitsubishi Chemical Corporation, “Product Data Sheet DIAION RCP160M” Summary of the Invention [Problem to be solved by the invention]

[0011] However, it has been newly discovered in the present invention that conventional biocomponent-adsorbing materials adsorb heparin as well as biocomponents, particularly cytokines, and thus have a problem in that the adsorption of both substances competes with each other.

[0012] When the biocomponent adsorbent material adsorbs heparin, the heparin concentration in the blood decreases, causing blood to clot. To prevent blood clotting, additional heparin must be administered, but in this case, the biocomponent adsorbent material becomes covered with heparin and no longer adsorbs cytokines, and administering a large amount of heparin into the body increases the possibility of causing serious side effects.

[0013] Patent Documents 1 to 4 do not include any idea regarding inhibition of competitive adsorption of cytokines and heparin.

[0014] Therefore, the present invention has newly discovered the problem that there is competition between the adsorption of biological components, particularly cytokines, and the adsorption of heparin, and in order to solve this problem, it is an object of the present invention to provide a biological component adsorption material that combines high adsorption capacity for biological components, particularly cytokines, with low adsorption capacity for heparin. [Means for solving the problem]

[0015] The present inventors have conducted intensive research to solve the above problems, and as a result, have discovered that a biocomponent adsorption material comprising a water-insoluble material consisting of a substrate containing a polymer having an aromatic ring in the repeating unit, sulfonic acid groups immobilized on the substrate, and a crosslinked structure that crosslinks the polymers to each other, exhibits both high adsorption capacity for biocomponents and low adsorption capacity for heparin when the content of sulfonic acid groups and water content are constant, thereby completing the present invention.

[0016] That is, the present invention includes the following (1) to (6). (1) A biocomponent adsorption material comprising a water-insoluble material comprising a substrate containing a polymer having an aromatic ring in the repeating unit, sulfonic acid groups immobilized on the substrate, and a crosslinked structure that crosslinks the polymers to each other, wherein the content of the sulfonic acid groups is 0.2 to 2.0 mmol per 1 g of the water-insoluble material, and the water content of the water-insoluble material is 60% or more and less than 100%. (2) The biocomponent-adsorbing material according to (1), wherein the water content is 60 to 95%. (3) The biocomponent-adsorbing material according to (1) or (2), wherein the polymer is polystyrene or a polystyrene derivative. (4) The biocomponent-adsorbing material according to any one of (1) to (3), wherein the maximum crosslinking rate of the polymer is more than 0 and not more than 1.00 mol %. (5) The biocomponent-adsorbing material according to any one of (1) to (3), wherein the crosslinked structure is derived from formaldehyde or a substituted benzaldehyde. (6) A biological component adsorption column comprising the biological component adsorption material according to any one of (1) to (5). Effect of the Invention

[0017] The biological component-adsorbing material of the present invention enables the administration of a reduced amount of anticoagulant, particularly in blood purification therapy, and allows treatment to be carried out safely. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The biocomponent adsorption material of the present invention comprises a water-insoluble material comprising a substrate containing a polymer having an aromatic ring in the repeating unit, a sulfonic acid group immobilized on the substrate, and a crosslinking structure that crosslinks the polymer, the content of the sulfonic acid group being 0.2-2.0 mmol per 1 g of the water-insoluble material, and the water content of the water-insoluble material being 60% or more and less than 100%. That is, the biocomponent adsorption material of the present invention comprises a water-insoluble material comprising a substrate in which polymers having an aromatic ring in the repeating unit are crosslinked to each other, and a sulfonic acid group immobilized on the substrate, the content of the sulfonic acid group being 0.2-2.0 mmol per 1 g of the water-insoluble material, and the water content of the water-insoluble material being 60% or more and less than 100%.

[0019] The term "substrate" refers to a material used in the biocomponent adsorption material to exhibit the biocomponent adsorption function, and the substrate in the present invention includes a polymer having an aromatic ring in the repeating unit. In order to maintain the strength of the material, the substrate may also include a polymer other than the polymer having an aromatic ring in the repeating unit (e.g., polyethylene, polypropylene), but it is preferable that at least half of the surface area of ​​the substrate is a polymer having an aromatic ring in the repeating unit.

[0020] "Polymer having an aromatic ring in the repeating unit" means a polymer containing an aromatic ring in the repeating unit. There is no particular limitation as long as the repeating unit contains an aromatic ring, and repeating units of multiple chemical structures may be contained. The aromatic ring is preferably, for example, a benzene ring, a naphthalene ring, or an acetylene ring, and more preferably contains a benzene ring because of the large number of reaction points. In addition, the polymer having an aromatic ring in the repeating unit may be a homopolymer consisting of one repeating unit, or a copolymer consisting of multiple repeating units.

[0021] Examples of polymers having an aromatic ring in the repeating unit include polystyrene or a derivative thereof (e.g., poly-p-chloromethylstyrene, poly-α-methylstyrene, poly-β-methylstyrene, poly-p-tert-butoxystyrene, poly-p-acetoxystyrene, or poly-p-(1-ethoxy)styrene), polysulfone or a derivative thereof, polyether ketone, polyphenylene sulfide, polyethylene terephthalate, or polyether ether ketone, from the viewpoint of having a proven track record in blood purification and having confirmed biocompatibility. Polystyrene or a derivative thereof, polysulfone or a derivative thereof, polyethylene terephthalate, polyether ketone, or polyether ether ketone are preferred from the viewpoint of less deterioration due to decomposition. Polystyrene or a derivative thereof, polysulfone or a derivative thereof, polyether ketone, or polyether ether ketone are more preferred from the viewpoint of less deterioration due to decomposition. Polystyrene or a derivative thereof, or polysulfone or a derivative thereof is even more preferred from the viewpoint of ease of reaction. Among these, polystyrene or a derivative thereof, in which an aromatic ring is present in the side chain that is easily accessible to biological components, is particularly preferred. The substitution position of the substituent on each aromatic ring does not matter.

[0022] The term "sulfonic acid group immobilized on a substrate" refers to a sulfonic acid group (-SO3H) immobilized on a substrate chemically (e.g., covalent bond or intermolecular force) or physically (e.g., entanglement or aggregation of polymers). There is no limitation on the bonding mode of immobilization, but a covalent bond is preferred from the viewpoint of avoiding elution. There is no particular limitation on the position of the covalent bond, but it is preferred that the sulfonic acid group is covalently bonded to an aromatic ring via a linker or directly from the viewpoint of ease of reaction, and it is more preferred that the sulfonic acid group is covalently bonded directly from the viewpoint of low decomposition of the bond and low elution. The sulfonic acid group in the present invention also includes sulfonate salts in which a proton is released and a counter cation (e.g., metal ions such as sodium ion, potassium ion, and calcium ion) is ionically bonded.

[0023] If the sulfonic acid group content is too low, it will not be able to interact with biological components, and if it is too high, the ability to adsorb biological components, particularly cytokines, will decrease and eluates will be more likely to be produced. Therefore, the sulfonic acid group content is 0.2 to 2.0 mmol per gram of the water-insoluble material, preferably 0.5 to 2.0 mmol, more preferably 1.0 to 2.0 mmol, and even more preferably 1.0 to 1.8 mmol.

[0024] The term "linker" refers to a chemical structure that exists between the substrate and the sulfonic acid group when immobilizing the substrate and the sulfonic acid group by a covalent bond. The chemical structure contained as the linker is preferably an electrically neutral chemical bond such as an aliphatic hydrocarbon, a urea bond, an ether bond, an ester bond, or an amide bond, and is preferably an aliphatic hydrocarbon or an ether bond because of its low decomposability.

[0025] The term "crosslinked structure" refers to a chemical bond in which a polymer having an aromatic ring in one repeating unit and a polymer having an aromatic ring in another repeating unit are bonded to each other. There is no limitation on the crosslinked structure, but from the viewpoint of being able to be introduced after molding of the polymer and being advantageous in processing, a crosslinked structure derived from an aldehyde is preferred, for example, a crosslinked structure derived from formaldehyde or a substituted benzaldehyde (e.g., benzaldehyde, p-diethylaminobenzaldehyde (DEAP), p-dimethylaminobenzaldehyde (DMAP) or p-isopropylbenzaldehyde (IPP)) is preferred, and from the viewpoint of avoiding coloring, formaldehyde is more preferred. When paraformaldehyde is used as a reagent, the crosslinked structure to be fixed is derived from formaldehyde, which is its decomposition product.

[0026] The "maximum crosslinking rate" is the maximum value of crosslinking of aromatic rings contained in the base material, expressed as a molar percentage. There are no upper or lower limits for the maximum crosslinking rate, but since it is difficult to control the water content within an appropriate range and exhibit performance when the crosslinked structure is increased, it is preferable that the maximum crosslinking rate is 1.00 mol% or less, and since elution is likely to occur when the maximum crosslinking rate is too low, it is preferable that the maximum crosslinking rate is more than 0 mol%, and more preferably 0.05 mol% or more.

[0027] The term "water-insoluble material" refers to a material that is composed of a substrate, a sulfonic acid group fixed to the substrate, and a crosslinked structure that crosslinks a polymer, and that is water-insoluble.

[0028] The substrate being water-insoluble means that the amount of the substrate dissolved in water is 1% by mass or less. 1 g of dried substrate is immersed in 10 mL of pure water at 37°C, and after 24 hours, the substrate alone is pulled up with tweezers, and the remaining water is dried in a vacuum dryer at 50°C. If the mass of the remaining solid is 10 mg or less, the amount of the substrate dissolved is 1% by mass or less, and the substrate is water-insoluble. If the substrate is not insoluble, there is a risk that the amount of elution will be large when actually used, which is undesirable from a safety standpoint.

[0029] The water content of the water-insoluble material is 60% or more and less than 100% from the viewpoint of expressing the function of adsorbing a biological component. If the water content is too high, elution is likely to occur, so the water content is preferably 60 to 95%, and more preferably 60 to 90%.

[0030] The content of the sulfonic acid group fixed to the substrate and the water content of the water-insoluble material may be combined in any desired manner.

[0031] There are no particular limitations on the color of the water-insoluble material, but since blood is reddish-black when it comes into contact with blood, if the material itself is colored, it will be difficult to see that blood has passed through it, making it difficult to work with, so colorless, white, or yellow, which makes it easy to see the shades of reddish-black, are preferred.

[0032] "Biocomponent adsorption material" means a material for adsorbing a biocomponent, and is not limited to a composition other than that containing a water-insoluble material, but may be a water-insoluble material alone or a composition in which the water-insoluble material maintains its shape and is mixed with a reinforcing material to appropriately exhibit its function, and from the viewpoint of high functionality, a water-insoluble material alone is preferable. The mixing operation may be performed at the stage of only the substrate before it becomes a water-insoluble material, or may be performed after the crosslinked structure and sulfonic acid group are fixed to the substrate.

[0033] The term "reinforcing material" refers to a material that does not have a function of adsorbing biological components by itself, and is mixed with the water-insoluble material to maintain its shape and to control the contact state with the biological components.

[0034] The material of the reinforcing material is not particularly limited, but examples thereof include polymeric materials not containing aromatic rings and hydroxyl groups in the repeating structure, such as homopolymers or copolymers of polyamide, polyacrylonitrile, polyethylene, polypropylene, nylon, polymethyl methacrylate, or polytetrafluoroethylene, or blends of these polymeric materials. Among these, polyethylene or polypropylene is preferred.

[0035] The shape of the biological component adsorption material may be a fiber shape, a flat membrane shape, a hollow fiber membrane shape, or a particle shape, with a fiber shape or a particle shape being preferred from the viewpoint of not forming a stagnation portion during blood contact. Furthermore, among the above-mentioned fiber shapes, processed fibers such as thread bundles, yarns, felts, nets, knitted fabrics, or woven fabrics are preferred, with thread bundles, knitted fabrics, or woven fabrics being more preferred in consideration of the large surface area and small flow resistance.

[0036] When the biocomponent-adsorbing material is in a particulate form, the particle size may be any size, but from the viewpoint of increasing the contact area and suppressing clogging, it is preferably 1 μm to 1 mm, more preferably 20 μm to 500 μm.

[0037] The "particle size" refers to the average value of the measured values ​​obtained by randomly collecting 10 particles as a sample, photographing each sample using a scanning electron microscope or the like, and measuring the diameter of the particle at 10 points in each photograph (a total of 100 points for all samples).

[0038] When the biocomponent adsorption material is in the form of fibers, the single fiber diameter may be any thickness, but from the viewpoint of increasing the contact area and maintaining the strength of the material, it is preferably 3 to 200 μm, more preferably 5 to 50 μm, and even more preferably 10 to 40 μm.

[0039] The "single yarn diameter" refers to the average value of the measurements taken by randomly selecting 10 small fiber samples, photographing each sample using a scanning electron microscope or the like, and measuring the fiber diameter at 10 points in each photograph (a total of 100 points for all samples).

[0040] When the biocomponent adsorption material is in the form of a fiber, the cross-sectional structure of the fiber may be, for example, a single yarn made of one type of polymer, or a core-sheath, sea-island or side-by-side type composite fiber. From the viewpoint of maintaining the strength of the material during blood purification, the core-sheath type composite fiber or sea-island type composite fiber is preferred.

[0041] When the biocomponent adsorption material is in the form of a knitted fabric, felt or net, it can be manufactured by a known method using a fibrous substrate or biocomponent adsorption material as a raw material. Examples of methods for manufacturing felt include the wet method, carding method, air laying method, spunbonding method and meltblowing method. Examples of methods for manufacturing knitted fabrics and nets include the plain weave method and tubular knitting method. In particular, knitted fabrics manufactured by the tubular knitting method are preferred from the viewpoint of having a large filling mass per unit volume and being filled into a blood purifier.

[0042] The term "biological component" refers to substances and cells present in a living body, and biological components in blood are suitable as biological components targeted by the present invention. Biological components in blood include not only blood components that originally constitute blood, but also biological components present in blood that originate from body fluids, tissues, organs, etc. other than blood, foreign pathogenic substances present in blood, pathogenic microorganisms and their secretions, etc. Blood components are further classified into liquid components in blood and cellular components in blood. There are no particular limitations on the biological components to be adsorbed by the biological component adsorption material of the present invention, but when used in blood purification therapy, blood components are preferred, and among blood components, liquid components in blood are more preferred.

[0043] "Cell components in blood" refers to floating cells contained in blood, and examples thereof include white blood cell components such as granulocytes, monocytes, and lymphocytes, red blood cells, platelets, etc. When the purpose is to treat inflammatory diseases, the subject of adsorption is preferably white blood cell components, and among white blood cell components, monocytes and granulocytes (including activated granulocytes, activated monocytes, activated granulocyte-activated platelet complexes, and activated monocyte-activated platelet complexes), which release inflammatory cytokines and can calm inflammatory diseases by removing them, are preferred.

[0044] "Activated granulocytes" and "activated monocytes" refer to granulocytes and monocytes, respectively, that release cytokines or reactive oxygen species due to cytokines, Lipopolysaccharide (LPS), etc. The degree of activation can be determined by measuring the amount of reactive oxygen species released by activated granulocytes or activated monocytes, or by measuring the expression of surface antigens by flow cytometry, etc.

[0045] The term "activated platelets" refers to platelets that release cytokines, active oxygen, and the like in response to cytokines, LPS, and the like.

[0046] The terms "activated granulocyte-activated platelet complex" and "activated monocyte-activated platelet complex" refer to activated granulocytes or activated monocytes bound to activated platelets, which have a phagocytic effect on autologous tissue. In particular, in the treatment of patients with inflammatory diseases, it is considered important to remove activated granulocyte-activated platelet complexes, which are thought to be directly involved in the pathology.

[0047] "Liquid components in blood" refers to organic substances dissolved in blood. Specific examples include low molecular weight organic compounds such as urea or amino acids, proteins such as β2-microglobulin, cytokines, IgE or IgG, polysaccharides such as LPS, and lipids such as LDL cholesterol or HDL cholesterol. Among these, proteins such as cytokines or polysaccharides such as LPS are preferred as adsorption targets, and cytokines are even more preferred as adsorption targets when the purpose is to treat inflammatory diseases.

[0048] The term "cytokine" refers to a group of proteins that are produced by various cells, including immunocompetent cells, in response to stimuli such as infection or trauma, and are released extracellularly to act. Examples of cytokines include interferon α, interferon β, interferon γ, interleukin 1 to interleukin 15, tumor necrosis factor α, tumor necrosis factor β, high mobility group box-1, erythropoietin, and monocyte chemotactic factor.

[0049] The term "inflammatory disease" refers to all diseases that induce an inflammatory response in the body, and examples thereof include systemic lupus erythematosus, malignant rheumatoid arthritis, multiple sclerosis, ulcerative colitis, Crohn's disease, drug-induced hepatitis, alcoholic hepatitis, hepatitis A, hepatitis B, hepatitis C, hepatitis D, hepatitis E, sepsis (e.g., gram-negative bacterial sepsis, gram-positive bacterial sepsis, culture-negative sepsis, and fungal sepsis), influenza, acute respiratory distress syndrome (ARDS; also written as acute respiratory distress syndrome or acute respiratory distress syndrome), acute lung injury (ALI), pancreatitis, idiopathic pulmonary fibrosis (IPF), reperfusion injury after organ transplantation, cholecystitis, cholangitis, and neonatal blood type incompatibility.

[0050] Among inflammatory diseases, the causative substances are released into the blood, and the therapeutic effect of blood purification is particularly expected, so that drug-induced hepatitis, alcoholic hepatitis, hepatitis A, hepatitis B, hepatitis C, hepatitis D, hepatitis E, sepsis (e.g., gram-negative bacteria-derived sepsis, gram-positive bacteria-derived sepsis, culture-negative sepsis, or fungal sepsis), influenza, acute respiratory distress syndrome, acute lung injury, pancreatitis, or idiopathic interstitial pneumonia are preferred as treatment targets. The biocomponent-adsorbing material of the present invention is preferably used, for example, for the treatment of the above-mentioned inflammatory diseases, and more preferably for the treatment of sepsis (e.g., gram-negative bacteria-derived sepsis, gram-positive bacteria-derived sepsis, culture-negative sepsis, or fungal sepsis), influenza, acute respiratory distress syndrome, acute lung injury, or idiopathic interstitial pneumonia, which are difficult to treat with drugs alone and are considered to involve both cytokines and activated leukocytes-activated platelets.

[0051] "Adsorption" refers to a state in which a specific substance adheres to a material and does not easily peel off. Examples of the principle of adsorption include a state in which a substance adheres to a material by van der Waals forces, such as ionic interactions, such as electrostatic interactions, hydrophobic interactions, or hydrogen bonds, and a state in which a substance adheres biologically, such as cell adhesion or phagocytosis by white blood cells.

[0052] The biocomponent adsorption material of the present invention is preferably used as a material to be packed in a container that forms the outer shape of a biocomponent adsorption column.

[0053] The shape of the container that forms the exterior of the biocomponent adsorption column may be any container that can be filled with a biocomponent adsorption material and has an inlet and outlet for a solution containing a biocomponent, and examples of such containers include cylindrical containers or prismatic containers such as triangular, square, hexagonal or octagonal prisms.

[0054] Furthermore, although there is no limitation on the use of the biocomponent adsorption column provided with the biocomponent adsorption material, the use of removing unnecessary biocomponents from a solution is preferable, and the use of removing proteins (e.g., cytokines) is more preferable. Specifically, the use of the column includes blood purification therapy, which is a use of removing pathogenic substances from body fluids (e.g., treatment of inflammatory diseases by removing cytokines from blood), and the use of removing unnecessary biocomponents from a solution containing biocomponents (e.g., removal of cytokines from organ preservation solutions for the purpose of maintaining the preservation state of organs removed for transplantation, removal of cytokines in the manufacturing process of cell preparations such as blood preparations, removal of biocomponents other than T cells when removing T cells in CAR-T therapy, removal of cytokines and cell membranes from iPS cell-derived platelets, regeneration of dialysis fluid by treating unnecessary proteins and urea in liquids such as dialysis fluid, and removal of unnecessary proteins derived from bacteria in the manufacturing process of biopharmaceuticals). Among these, the column can be preferably used for blood purification therapy, in which removal of inflammatory cytokines is effective. When a biological component adsorption column is used in blood purification therapy, an extracorporeal circulation method is preferred in which an adsorption column equipped with the biological component adsorption material is connected to a patient via a blood circuit, and body fluid extracted from the patient is passed through the biological component adsorption column and then returned to the patient. From the viewpoint of suppressing further inflammation induction by biological components, the treatment time for the body fluid, etc. is preferably continuous treatment, more preferably 4 hours or more, and even more preferably 24 hours or more.

[0055] The biocomponent adsorption column comprising the biocomponent adsorption material may be used in combination with other body fluid treatment methods or medical devices. Examples of other body fluid treatment methods and medical devices include plasma exchange, peritoneal dialysis, plasma separators, hemofilters, heart-lung machines, and extracorporeal membrane oxygenation (ECMO). The biocomponent adsorption material or the biocomponent adsorption column may be incorporated as a component of these medical devices.

[0056] The maximum crosslinking rate of the water-insoluble material is obtained by dividing the molar amount of the crosslinker added when the water-insoluble material is prepared by the weight of the substrate added when the water-insoluble material is prepared, and then dividing the result by the molar amount of aromatic rings in the substrate.

[0057] The moisture content of the water-insoluble material can be obtained by converting sulfonic acid groups in the water-insoluble material to sodium sulfonate, allowing it to absorb water, suction filtering, and using the value when the weight stabilizes as the wet weight, and the value after vacuum drying as the dry weight, and then subtracting the dry weight from the wet weight to calculate the moisture amount, and then dividing the moisture amount by the dry weight.

[0058] The content of sulfonic acid groups in the water-insoluble material can be determined by measuring the dry weight of the water-insoluble material after drying, subjecting the sulfonic acid groups in the water-insoluble material to ion exchange with sodium chloride, and back titrating the supernatant solution with an aqueous sodium hydroxide solution.

[0059] When the biocomponent adsorption material contains a reinforcing material, the maximum crosslinking rate, water content, or sulfonic acid group content of the water-insoluble material is measured after extracting only the water-insoluble material by dissolving the reinforcing material contained in the biocomponent adsorption material in a solvent that dissolves only the reinforcing material, or by physically separating the reinforcing material.

[0060] In blood purification therapy in which a biocomponent adsorption material is used as a biocomponent adsorption column, the typical usage time is within 24 hours, so if the absorbance of the eluate (hereinafter referred to as "eluate absorbance") when elution is performed at 70°C for 24 hours is low, it can be determined that elution during use is sufficiently suppressed. From the viewpoint of simplifying the preliminary cleaning work before using the biocomponent adsorption column, the eluate absorbance is preferably 0.01 or less, and more preferably 0.005 or less.

[0061] The absorbance of the eluate is obtained by adding a specified area of ​​the biocomponent-adsorbing material to distilled water, shaking at 70°C for 24 hours to elute the material, and measuring the absorbance of the resulting supernatant solution at 220 nm using an ultraviolet-visible spectrophotometer.

[0062] The biocomponent-adsorbing material of the present invention can be produced, for example, by the following method, but is not limited to this method.

[0063] The substrate can be a commercially available one as it is. When processing is required to mold the substrate into any shape such as a fiber shape, a flat membrane shape, a hollow fiber membrane shape, or a particle shape, a commercially available resin can be purchased, heated and melted, and discharged from a die, or dissolved in a good solvent and then discharged from a die into a poor solvent or into the atmosphere, thereby forming the substrate into any shape. Alternatively, a particle-shaped substrate can be prepared by dissolving a polymer material to be the substrate in a good solvent, dropping the solution of the polymer material into a poor solvent, and then desolvating the polymer to flocculate the polymer, or by precipitation simultaneously with polymerization by suspension polymerization. When a reinforcing material is mixed with the substrate, it can be mixed by, for example, mixing and molding during processing of the substrate, or by physically mixing by needle punching after processing.

[0064] The substrate having the fixed crosslinked structure can be reacted and bonded by dissolving a crosslinking agent in an aprotic solvent in the presence of an acid catalyst and impregnating the substrate or the substrate and reinforcing material therein.

[0065] The crosslinking agent, acid catalyst and aprotic solvent may be commercially available and used as they are.

[0066] As the acid catalyst, for example, sulfuric acid is preferably used, and as the aprotic solvent, for example, nitrobenzene is preferably used. The impregnation temperature is preferably 0 to 40°C, more preferably 10 to 20°C, from the viewpoint of suppressing deformation of the substrate and side reactions while reacting. The reaction time is preferably 1 minute to 2 hours, more preferably 1 to 30 minutes, from the viewpoint of suppressing side reactions, dissolution, and deformation. The solid-liquid ratio is preferably 40 to 80 g per 1 g of substrate, more preferably 50 to 60 g, from the viewpoint of appropriately impregnating the substrate. The amount of the crosslinking agent added is preferably 1 to 10 mmol per 1 mol of aromatic rings in the substrate, from the viewpoint of appropriately controlling the maximum crosslinking rate.

[0067] The water-insoluble material can be obtained by impregnating a substrate having a crosslinked structure fixed thereon, or a substrate having a crosslinked structure fixed thereon and a reinforcing material, with sulfuric acid or a mixed solvent of sulfuric acid and an aprotic solvent, and reacting and bonding the sulfonic acid groups. When the reinforcing material is mixed in advance, the material can be used as it is as a biocomponent-adsorbing material, and the water-insoluble material can also be used as it is as a biocomponent-adsorbing material.

[0068] As the aprotic solvent, for example, nitrobenzene is preferably used.

[0069] The concentration of sulfuric acid is, for example, 30 to 90 wt%, preferably 50 to 90 wt%, from the viewpoint of achieving reactivity. The impregnation temperature is preferably 0 to 100° C., more preferably 30 to 70° C., from the viewpoint of suppressing deformation of the substrate and side reactions while reacting. The impregnation time is preferably 30 minutes to 6 hours, more preferably 1 to 3 hours, from the viewpoint of sufficiently bonding the sulfonic acid groups.

[0070] When mixing a water-insoluble material with a reinforcing material to produce a biocomponent adsorption material, the water-insoluble material can be mixed to produce a biocomponent adsorption material by, for example, needle-punching the water-insoluble material into the reinforcing material, or by cutting the material into small pieces and mixing them into the reinforcing material.

[0071] The water content of the water-insoluble material can be increased, for example, by decreasing the maximum crosslinking rate or increasing the content of sulfonic acid groups.

[0072] The maximum crosslinking rate of the water-insoluble material can be reduced by lowering the amount of crosslinker added.

[0073] The content of sulfonic acid groups in the water-insoluble material can be reduced by, for example, lowering the impregnation temperature, lowering the sulfuric acid concentration, or shortening the impregnation time.

[0074] One method for evaluating the adsorption capacity of a biocomponent adsorption material for liquid components in blood is to impregnate the biocomponent adsorption material with fetal bovine serum (FBS) in which cytokines have been dissolved, measure the decrease in cytokine concentration in the FBS before and after impregnation, and calculate the cytokine adsorption rate.

[0075] Since cytokines are substances that are preferably removed from the blood in order to improve the pathology of inflammatory diseases, it can be determined that the greater the reduction in cytokine concentration due to impregnation into the biocomponent adsorbing material, the higher the biocomponent adsorption ability, particularly the blood component adsorption ability. Preferred cytokines to be removed include interleukin 1β, interleukin 6, interleukin 8, high mobility group protein-1, tumor necrosis factor-β, etc., and interleukin 6 is more preferred as the adsorption target in the treatment of inflammatory diseases.

[0076] One method for evaluating the heparin adsorption ability of a biocomponent adsorption material is to immerse the biocomponent adsorption material in saline solution containing dissolved heparin, measure the decrease in heparin concentration in the saline solution before and after impregnation, and calculate the heparin adsorption rate.

[0077] Heparin is a substance added when the biocomponent-adsorbing material is used in blood purification therapy for the treatment of inflammatory diseases, but if the biocomponent-adsorbing material adsorbs a large amount of heparin, a higher concentration of heparin must be administered, and there is a high risk that competitive adsorption will prevent the blood component adsorption performance from being fully expressed. Therefore, the greater the decrease in heparin concentration due to impregnation with the biocomponent-adsorbing material, the less preferable the biocomponent-adsorbing material can be determined to be.

[0078] The adsorption of interleukin 6 and heparin to the above-mentioned biocomponent adsorption material is thought to be a Langmuir-type equilibrium reaction in which the surface is covered with a single layer, and therefore it is thought that adsorption equilibrium will be reached after approximately 4 hours of adsorption treatment, regardless of the concentration of the substance to be adsorbed.

[0079] For the reasons stated above, it is preferable that the interleukin 6 adsorption rate of the biological component adsorption material is 100% after 4 hours of adsorption treatment, and since it is time-dependent, a rate of 50% or more after 2 hours of adsorption treatment can be considered to have sufficient adsorption capacity.

[0080] Furthermore, when the adsorption equilibrium constant of heparin to the biocomponent adsorption material is smaller than that of interleukin-6, a portion of the heparin coating the surface of the biocomponent adsorption material is replaced by interleukin-6, suppressing competitive adsorption.

[0081] For the above reasons, the interleukin 6 adsorption rate of the biocomponent adsorption material of the present invention must be higher than the heparin adsorption rate, and if the heparin adsorption rate of the biocomponent adsorption material is less than 50% after 2 hours of adsorption treatment, it can be considered that the adsorption equilibrium constant is lower than that of interleukin 6 and that the adsorption of heparin is suppressed. The ratio of the interleukin 6 adsorption rate to the heparin adsorption rate must be greater than 1, and more preferably 2 or more. EXAMPLES

[0082] The biocomponent adsorption material of the present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, the weight of the biocomponent adsorption material is the dry weight. In addition, since no reinforcing material was used in the following examples, the biocomponent adsorption material was treated as synonymous with a water-insoluble material.

[0083] 1. Manufacturing method <Preparation of substrate A> Atactic (non-crystalline) polystyrene as the sea component and polypropylene as the island component were melt-weighed separately and fed into a spin pack equipped with a sea-island composite spinneret with 704 distribution holes for the island components per nozzle to form a sea-island composite flow, which was melt-extruded. The island ratio was controlled to 50wt%, and a fiber with a single fiber size of 7.1dtex (diameter 30μm) (hereinafter referred to as fiber A) was obtained.

[0084] Using fiber A, adjust the density adjustment scale of a tubular knitting machine (model name: circular knitting machine MR-1, Maruzen Sangyo Co., Ltd.) to obtain a weight of 0.0039 g / cm 2 , bulk density is 0.22g / cm 3 A cylindrical knitted fabric (hereinafter, referred to as substrate A; molar amount of polystyrene repeating units per 1 g: 4.81 mmol) was produced.

[0085] <Preparation of substrate B> Fiber B was prepared according to the method described in Patent Document 1, and then knitted with a cylindrical knitting machine and the sea layer was removed to obtain substrate B. The specific preparation method is described below.

[0086] Using the following components, a sea-island composite fiber having 36 islands, in which the islands were further configured as a core-sheath composite fiber (hereinafter, fiber B), was obtained under spinning conditions of a spinning speed of 800 m / min and a draw ratio of 3 times. Island core material: Polypropylene Island sheath composition: 90wt% polystyrene, 10wt% polypropylene Sea component: Copolymer polyester with ethylene terephthalate units as the main repeating unit and containing 3 wt% of 5-sodium sulfoisophthalic acid as a copolymer component. Composite ratio (weight ratio): Core: Sheath: Sea = 45:40:15

[0087] Using fiber B, adjust the density adjustment scale of the tubular knitting machine (model name: circular knitting machine MR-1, Maruzen Sangyo Co., Ltd.) to obtain a weight of 0.0065 g / cm 2 , bulk density is 0.35g / cm 3 The cylindrical knit was then treated with a 3 wt% aqueous solution of sodium hydroxide at 95°C to decompose and dissolve the sea component, resulting in a core-sheath fiber with a diameter of 5 μm and a basis weight of 0.0045 g / cm. 2 , bulk density is 0.26g / cm 3 A cylindrical knitted fabric (hereinafter referred to as substrate B; molar amount of polystyrene repeating units per 1 g: 4.33 mmol) was produced.

[0088] <Preparation of substrate C> Fiber C was prepared according to the method described in Patent Document 2 to obtain substrate C. The specific preparation method is described below.

[0089] A mixed polymer of 90 wt% polystyrene (weight average molecular weight 180,000) and 10 wt% polypropylene was used as the sea component, and polypropylene was used as the island component. The sea-island composite fiber (hereinafter referred to as fiber C) was produced by melt spinning using a composite spinneret, with 16 islands, a sea / island ratio of 50 / 50 wt%, and a fiber diameter of 20 μm.

[0090] Using fiber C, adjust the density adjustment scale of a tubular knitting machine (model name: circular knitting machine MR-1, Maruzen Sangyo Co., Ltd.) to obtain a weight of 0.0053 g / cm 2 , bulk density is 0.38g / cm 3 A cylindrical knitted fabric (hereinafter referred to as substrate C; molar amount of polystyrene repeating units per 1 g: 4.33 mmol) was produced.

[0091] <Preparation of substrate D> 20 g of atactic polystyrene pellets were dissolved in 200 g of dichloromethane to prepare a polymer solution. 300 mL of ion-exchanged water was placed in a 500 mL separable flask, 0.5 g of polyvinyl alcohol (PVA) was added, and the solution was stirred at 300 rpm using a three-one motor to prepare a PVA solution. Next, 4 mL of the polymer solution was filled into a 5 mL syringe, and a connected needle (inner diameter 0.23 mm) was inserted into the PVA solution being stirred by a three-one motor, and the polymer solution was discharged over 5 minutes and re-precipitated to obtain particles. The solution was stirred for 1 hour. Only the obtained particles were collected by sucking with a pipette and collected in a centrifuge tube. The remaining solution was subjected to the same procedure of discharging the polymer solution and collecting the precipitate, and this was repeated until all of the polymer solution was used up. The particles collected in the centrifuge tube were vacuum-dried for 24 hours to obtain 17 g of substrate D (polystyrene repeating unit molar amount per 1 g: 9.62 mmol / g) made of polystyrene particles. The particle size of the obtained particles was 35 μm.

[0092] <Preparation of Substrate E> Chloromethyl polystyrene resin 2% divinylbenzene (DVB) crosslinked (Tokyo Chemical Industry Co., Ltd., C1745) in the form of powder (particles) was used as the base material E. The particle diameter of the base material E was 113 μm. In addition, since the base material E was 2% DVB crosslinked, the maximum crosslinking rate was considered to be 2.00%.

[0093] <Creating substrate F> Using cellulose fibers (fiber diameter 50 μm), the density adjustment scale of a cylindrical knitting machine (model name: circular knitting machine MR-1, Maruzen Sangyo Co., Ltd.) was adjusted to obtain a weight of 0.0076 g / cm 2 , bulk density is 0.65g / cm 3 A cylindrical knitted fabric (hereinafter, referred to as substrate F; molar amount of cellulose repeating units per 1 g: 6.17 mmol) was produced.

[0094] <Preparation of biocomponent adsorption material 1> 180mL of nitrobenzene and 120mL of sulfuric acid were mixed in a 500mL Erlenmeyer flask and cooled to 10℃, and 36mg of paraformaldehyde (hereinafter referred to as PFA) (1.20mmol as formaldehyde) was added as a crosslinking agent, and the mixture was stirred until it was visually confirmed that the PFA had dissolved to obtain solution A. Furthermore, 180mL of nitrobenzene and 120mL of sulfuric acid were mixed and placed in another 500mL Erlenmeyer flask, and the mixture was heated to 50℃ to obtain solution B. 10g of pre-dried substrate A was impregnated in solution A for 5 minutes to cause a crosslinking reaction at 10℃. After the reaction, substrate A was removed with stainless steel tweezers and immediately impregnated in solution B to perform a sulfonic acid group introduction reaction for 1.5 hours. The obtained substrate A after the reaction was placed on a glass filter, and 500mL of methanol was added and suction filtration was performed. The addition of 500mL of methanol and suction filtration were repeated a total of 5 times. 500mL of water was then added and suction filtration was performed. The addition of 500 mL of water and suction filtration were repeated a total of five times to obtain biocomponent-adsorbing material 1.

[0095] <Preparation of biocomponent adsorption material 2> A biocomponent-adsorbing material 2 was obtained in the same manner as in the preparation of the biocomponent-adsorbing material 1, except that the amount of PFA added was changed from 36 mg to 3.6 mg (0.120 mmol as formaldehyde).

[0096] <Preparation of biocomponent adsorption material 3> A biocomponent-adsorbing material 3 was obtained in the same manner as in the preparation of the biocomponent-adsorbing material 1, except that the amount of PFA added was changed from 36 mg to 3.0 mg (0.100 mmol as formaldehyde).

[0097] <Preparation of biocomponent adsorption material 4> Biocomponent adsorption material 4 was obtained using the same method as for preparing biocomponent adsorption material 1, except that the amount of PFA added was changed from 36 mg to 3.0 mg (0.100 mmol as formaldehyde) and the reaction time for introducing sulfonic acid groups was changed from 1.5 hours to 0.25 hours.

[0098] <Preparation of biocomponent adsorption material 5> Biocomponent adsorption material 5 was obtained using the same method as for preparing biocomponent adsorption material 1, except that the amount of PFA added was changed from 36 mg to 1.8 mg (0.060 mmol as formaldehyde) and the reaction time for introducing sulfonic acid groups was changed from 1.5 hours to 1.0 hour.

[0099] <Preparation of biocomponent adsorption material 6> Biocomponent adsorption material 6 was obtained using the same method as for preparing biocomponent adsorption material 1, except that the amount of PFA added was changed from 36 mg to 3.0 mg (0.100 mmol as formaldehyde) and the reaction time for introducing sulfonic acid groups was changed from 1.5 hours to 2.0 hours.

[0100] <Preparation of biocomponent adsorption material 7> Biocomponent-adsorbing material 7 was obtained using the same method as for preparing biocomponent-adsorbing material 1, except that the crosslinking agent was changed from PFA to DEAP and the amount of crosslinking agent added was changed from 36 mg to 72 mg (0.373 mmol as DEAP).

[0101] <Preparation of biocomponent adsorption material 8> Biocomponent-adsorbing material 8 was obtained using the same method as for preparing biocomponent-adsorbing material 1, except that the crosslinking agent was changed from PFA to DMAP and the amount of crosslinking agent added was changed from 36 mg to 66 mg (0.443 mmol as DMAP).

[0102] <Preparation of biocomponent adsorption material 9> Biocomponent-adsorbing material 9 was obtained using the same method as for preparing biocomponent-adsorbing material 1, except that the crosslinking agent was changed from PFA to IPP and the amount of crosslinking agent added was changed from 36 mg to 66 mg (0.446 mmol as IPP).

[0103] <Preparation of Biological Component Adsorption Material 10> A biocomponent-adsorbing material 10 was obtained using the same method as for producing the biocomponent-adsorbing material 1, except that the amount of the crosslinking agent added was changed from 36 mg to 0.6 mg (0.020 mmol as formaldehyde).

[0104] <Preparation of biocomponent adsorption material 11> The biocomponent-adsorbing material 11 was obtained in the same manner as in the preparation of the biocomponent-adsorbing material 1, except that the amount of PFA added was changed from 36 mg to 0 mg and the reaction time for introducing sulfonic acid groups was changed from 1.5 hours to 0.25 hours.

[0105] <Preparation of biocomponent adsorption material 12> The biocomponent-adsorbing material 12 was obtained in the same manner as in the preparation of the biocomponent-adsorbing material 1, except that the amount of PFA added was changed from 36 mg to 3.0 mg and the reaction time for introducing sulfonic acid groups was changed from 1.5 hours to 4 hours.

[0106] <Preparation of biocomponent adsorption material 13> Using the substrate B, a biocomponent-adsorbing material 13 was obtained using the same method as in "Preparation of methylsulfoethanamine-modified nonwoven fabric" in Patent Document 1. The preparation method is shown below.

[0107] Nitrobenzene 46wt%, sulfuric acid 46wt%, paraformaldehyde 1wt%, N-methylol-α-chloroacetamide (hereinafter referred to as NMCA) 7wt% were mixed, stirred and dissolved at 10℃ or less to prepare an NMCA reaction solution. This NMCA reaction solution was brought to 5℃, and 400mL of the NMCA reaction solution was added to 10g of substrate B, and the reaction solution was kept at 5℃ in a water bath for 2 hours. After that, substrate B was taken out of the reaction solution and immersed in the same amount of nitrobenzene as the NMCA reaction solution and washed. Then, it was immersed in methanol and washed to obtain substrate B after the reaction. The mass of paraformaldehyde added in this process was 6g (200mmol as formaldehyde).

[0108] Furthermore, 4.2 g of N-methyltaurine and 5 g of potassium iodide were added to 500 mL of DMSO, and triethylamine was added thereto so that the concentration became 473 mM, and 10 g of the reacted substrate B was immersed in the mixed solution and reacted at 60° C. for 6 hours. After the reaction, the substrate B was washed with DMSO and methanol, and further washed with water to obtain a biocomponent adsorbing material 13, which is the methylsulfoethanaminated substrate B.

[0109] <Preparation of biocomponent adsorption material 14> A biocomponent-adsorbing material 14 was obtained using the substrate C and the same method as used for producing the protein-adsorbing fiber B described in Patent Document 2. The production method is described below.

[0110] 181 mL of nitrobenzene, 119 mL of sulfuric acid, and 4 g (27.02 mmol) of IPP were mixed, stirred, and dissolved at 50°C to prepare 300 mL of reaction solution. 10 g of substrate C was immersed in this reaction solution, and the reaction solution was kept at 50°C for 1 hour. After that, the reacted fiber was removed from the reaction solution and immersed in 40 mL of nitrobenzene for washing. Next, it was immersed in methanol for washing, and further immersed in water for washing, to obtain biocomponent adsorption material 14 crosslinked by IPP.

[0111] <Preparation of biocomponent adsorption material 15> Biocomponent adsorption material 15 was prepared using the same method as for preparing biocomponent adsorption material 1, except that the amount of PFA added was changed from 36 mg to 0 mg and the reaction time for introducing sulfonic acid groups was changed from 1.5 hours to 2 hours. However, the base material dissolved, the shape could not be maintained, and the material became unusable.

[0112] <Preparation of biocomponent adsorption material 16> 180 mL of nitrobenzene and 120 mL of sulfuric acid were added to a 500 mL Erlenmeyer flask, and a stirrer was inserted and the mixture was heated to 60 ° C. while stirring with a magnetic stirrer. When the solution temperature reached 60 ° C., 5 g of pre-dried substrate D was gradually added while maintaining stirring, and the mixture was impregnated for 15 minutes to carry out a sulfonic acid group introduction reaction. The solution and stirrer in the Erlenmeyer flask were decanted, and 500 mL of ice-cooled methanol was added, followed by further decantation. The addition and decantation of 500 mL of methanol was repeated a total of five times. Next, 500 mL of water was added and decanted. The addition and decantation of 500 mL of water was repeated a total of five times, and the substrate D after the reaction was sucked up with a pipette and placed in a centrifuge tube to obtain a biocomponent adsorbent material 16.

[0113] <Preparation of biocomponent adsorption material 17> In a 500mL Erlenmeyer flask, 180mL of nitrobenzene, 120mL of sulfuric acid, 66mg of DMAP as a crosslinking agent (0.443mmol as DMAP), and a stirrer were placed and heated to 60℃ while stirring with a magnetic stirrer. 5g of pre-dried substrate D was gradually added while maintaining stirring, and impregnated for 15 minutes to simultaneously carry out crosslinking reaction and sulfonic acid group introduction reaction. The solution in the Erlenmeyer flask and the stirrer were decanted, and 500mL of ice-cooled methanol was added, and further decanted. The addition of 500mL of methanol and decantation were repeated a total of five times. Next, 500mL of water was added and decanted. The addition of 500mL of water and decantation were repeated a total of five times, and the substrate D after the reaction was sucked up with a pipette and placed in a centrifuge tube to obtain a biocomponent adsorbent material 17.

[0114] <Preparation of biocomponent adsorption material 18> In a 500mL Erlenmeyer flask, 180mL of nitrobenzene, 120mL of sulfuric acid, 66mg of DMAP as a crosslinking agent (0.443mmol as DMAP), and a stirrer were placed and heated to 60℃ while stirring with a magnetic stirrer. 5g of pre-dried substrate D was gradually added while maintaining stirring, and impregnated for 4 hours to simultaneously carry out crosslinking reaction and sulfonic acid group introduction reaction. The solution in the Erlenmeyer flask and the stirrer were decanted, and 500mL of ice-cooled methanol was added, and further decanted. The addition of 500mL of methanol and decantation were repeated a total of 5 times. Next, 500mL of water was added and decanted. The addition of 500mL of water and decantation were repeated a total of 5 times, and the substrate D after the reaction was sucked up with a pipette and placed in a centrifuge tube to obtain a biocomponent adsorbent material 18.

[0115] <Preparation of biocomponent adsorption material 19> 180 mL of nitrobenzene and 120 mL of sulfuric acid were added to a 500 mL Erlenmeyer flask, and a stirrer was added and the mixture was heated to 60 ° C. while stirring with a magnetic stirrer. When the solution temperature reached 60 ° C., 2 g of pre-dried substrate E was gradually added while maintaining stirring, and the mixture was impregnated for 15 minutes to carry out a sulfonic acid group introduction reaction. The solution and stirrer in the Erlenmeyer flask were decanted, and 500 mL of ice-cooled methanol was added, followed by further decantation. The addition and decantation of 500 mL of methanol was repeated a total of five times. Next, 500 mL of water was added and decanted. The addition and decantation of 500 mL of water was repeated a total of five times, and the substrate E after the reaction was sucked out with a pipette and placed in a centrifuge tube to obtain a biocomponent adsorbent material 19.

[0116] <Preparation of Biological Component Adsorption Material 20> 300mL of 0.1N hydrochloric acid and 9.3mg of PFA (0.31mmol as formaldehyde) were added to a 500mL Erlenmeyer flask, and the mixture was stirred until the PFA was dissolved. 10g of dried substrate F was immersed in this solution for 1 hour to cause a crosslinking reaction at 25°C. The substrate F after the reaction was removed with tweezers and placed in an empty 500mL Erlenmeyer flask, to which 300mL of 6N potassium hydroxide aqueous solution was added, and the mixture was immersed at 25°C for 5 minutes to swell the substrate F after the reaction. In addition, 300mL of ion-exchanged water and 10g of sodium chloroethanesulfonate were added to another 500mL Erlenmeyer flask, and the mixture was stirred until the sodium chloroethanesulfonate was dissolved. The swollen substrate F was added to this solution to perform a sulfonic acid group introduction reaction. The obtained substrate F was placed on a glass filter, 500mL of methanol was added, and the mixture was filtered by suction. The addition of 500mL of methanol and suction filtration were repeated a total of five times. Subsequently, 500 mL of water was added and suction filtration was performed. The addition of 500 mL of water and suction filtration were repeated a total of five times to obtain a biocomponent-adsorbing material 20.

[0117] 2. Evaluation Method <Maximum cross-linking ratio of water-insoluble material contained in biocomponent adsorption material 1> The maximum crosslinking rate of the water-insoluble material contained in the biocomponent-adsorbing material 1 was calculated from the amount of crosslinker added in the preparation of the biocomponent-adsorbing material 1, the weight of the base material added in the preparation of the biocomponent-adsorbing material 1, and the amount of aromatic rings contained in the base material using the following formula 1, rounded off to two decimal places. The results are shown in Table 1. Maximum crosslinking rate (mol%) = amount of crosslinker added in the preparation of the biocomponent-adsorbing material [mmol] ÷ (amount of aromatic rings contained in the base material used in the preparation of the biocomponent-adsorbing material 1 [mmol / g] × weight of base material added in the preparation of the biocomponent-adsorbing material [g]) × 100 Formula 1

[0118] <Measurement of water content of water-insoluble materials contained in biocomponent adsorption material 1> The biocomponent adsorption material 1 was cut into four circular pieces with a diameter of 30 mm and placed in a 50 mL polypropylene centrifuge tube with tweezers. Then, 25 mL of 6 M sodium hydroxide solution was added and mixed by inversion for 30 minutes to replace the sulfonic acid group with a sodium sulfonate group. After decanting the solution, Otsuka distilled water (manufactured by Otsuka Pharmaceutical Factory) was added and washed by inversion for 30 minutes. Phenolphthalein aqueous solution was added to the washing solution, and Otsuka distilled water (manufactured by Otsuka Pharmaceutical Factory) was added repeatedly until the reddish purple coloring was no longer observed, and the solution was washed until it became neutral. The biocomponent adsorption material 1 was removed with tweezers and placed on a glass filter. After suction filtration for 5 minutes and weight measurement with an electronic balance, it was placed back on the glass filter with tweezers again. Suction filtration and weight measurement were repeated, and the weight measurement when the difference between the previous weight measurement and the current weight measurement was within 1% of the current weight measurement was taken as the wet weight of the biocomponent adsorption material 1. Biocomponent-adsorbing material 1 was removed from the glass filter with tweezers and placed in a 500 mL polypropylene centrifuge tube, heated to 40°C, and dried under reduced pressure in a vacuum dryer for at least 24 hours. The weight measured after this was recorded as the dry weight. The water content of the water-insoluble material contained in biocomponent-adsorbing material 1 was calculated using the wet weight and dry weight of biocomponent-adsorbing material 1 and the following formula 2, with the obtained value rounded off to one decimal place. The results are shown in Table 1. Moisture content [%] = 100 × (moisture weight [mg] of biocomponent-adsorbing material - dry weight [mg] of biocomponent-adsorbing material) / (dry weight [mg] of biocomponent-adsorbing material) Equation 2

[0119] <Measurement of the sulfonic acid group content of water-insoluble materials contained in biocomponent adsorption material 1> Approximately 1 g of biocomponent adsorption material 1 and 20 mL of 6 M hydrochloric acid were added to a 50 mL polypropylene centrifuge tube, and the sulfonic acid group was desalted by mixing by inversion for 30 minutes at room temperature. After mixing, only the solution was decanted, 20 mL of ion-exchanged water was added, and the tube was mixed by inversion for 5 minutes. After mixing, the solution was decanted, 20 mL of ion-exchanged water was added, and the tube was mixed by inversion for 5 minutes. This operation was repeated 10 times, and the pH of the final decanted solution was determined with litmus paper and confirmed to be pH 6 or higher. After washing, the biocomponent adsorption material 1 was dried under reduced pressure for more than 24 hours in a vacuum dryer heated to 40°C.

[0120] 1.0 g of the obtained dried biocomponent adsorption material 1 was cut out and placed in a 50 mL polypropylene centrifuge tube, 30 mL of physiological saline was added, and the mixture was mixed by inversion for 30 minutes. 15 mL of the supernatant solution was removed from the centrifuge tube and placed in another 50 mL polypropylene centrifuge tube, and 0.02 mL each of a methyl red aqueous solution and a phenolphthalein aqueous solution was added. 0.02 mL of a 0.05 M sodium hydroxide aqueous solution was dropped into the centrifuge tube using a burette (Shibata Scientific, 021110-10), and the color of the solution was confirmed after 10 inversions. Dropping of the sodium hydroxide aqueous solution, inversion mixing, and color confirmation were repeated, and the amount of sodium hydroxide aqueous solution dropped when it was first observed that the color of the solution changed from red-orange to yellow was the titration amount. Using the titration amount and the following formula 3, the obtained value was rounded off to two decimal places to calculate the content (mmol / g) of sulfonic acid groups per 1 g of the water-insoluble material contained in the biocomponent-adsorbing material 1. The results are shown in Table 1. Sulfonic acid content [mmol / g] = {30 [mL] / 15 [mL]} × titer per 1 g [mL / g] × 0.05 [mol / L] Equation 3

[0121] <Maximum cross-linking ratio of water-insoluble materials contained in biocomponent adsorption materials 2 to 14, 16 to 18 and 20> The maximum crosslinking rates of the water-insoluble materials contained in the biocomponent-adsorptive materials 2 to 14 were calculated in the same manner as in the measurement of the maximum crosslinking rate of the biocomponent-adsorptive material 1. The results are shown in Table 1.

[0122] <Measurement of moisture content of water-insoluble materials contained in biocomponent adsorption materials 2-14 and 20> The moisture contents of the water-insoluble materials contained in the biocomponent-adsorptive materials 2 to 14 and 20 were calculated in the same manner as in the measurement of the moisture content of the biocomponent-adsorptive material 1. The results are shown in Table 1.

[0123] <Measurement of the sulfonic acid group content of water-insoluble materials contained in biocomponent adsorption materials 2-14 and 20> The contents of sulfonic acid groups in the water-insoluble materials contained in biocomponent-adsorbing materials 2 to 14 and 20 were calculated in the same manner as in the measurement of the content of sulfonic acid groups in the water-insoluble material contained in biocomponent-adsorbing material 1. The results are shown in Table 1.

[0124] <Maximum cross-linking ratio of water-insoluble material contained in biocomponent adsorption material 19> The maximum cross-linking rate of the biocomponent-adsorbing material 19 was considered to be 2%, since it was equivalent to the maximum cross-linking rate of the base material E. The results are shown in Table 1.

[0125] <Measurement of moisture content of water-insoluble materials contained in biocomponent adsorption materials 16-19> The biocomponent adsorption material 16 was sucked up with a 1 mL pipette and placed in a 50 mL polypropylene centrifuge tube. Then, 25 mL of 6 M sodium hydroxide solution was added and mixed by inversion for 30 minutes to replace the sulfonic acid group with a sodium sulfonate group. After decanting the solution, Otsuka distilled water (manufactured by Otsuka Pharmaceutical Factory) was added and washed by inversion for 30 minutes. Phenolphthalein aqueous solution was added to the washing solution, and Otsuka distilled water (manufactured by Otsuka Pharmaceutical Factory) was repeatedly added until the reddish purple coloring was no longer observed, and the solution was washed until it became neutral. The biocomponent adsorption material 16 was removed as much as possible with a pipette and placed on a glass filter with filter paper laid on it. The solution was filtered by suction for 5 minutes, and the particles were scraped and collected with a spatula as much as possible, and the weight was measured on an electronic balance, and then the solution was placed back on the glass filter with new filter paper laid on it. Suction filtration and weight measurement were repeated, and the weight measurement when the difference between the previous weight measurement and the current weight measurement was within 1% of the current weight measurement was taken as the wet weight of the biocomponent adsorbent material 16. The biocomponent adsorbent material 16 was scraped off from the filter paper with a spatula, placed in a 50 mL polypropylene centrifuge tube, and dried under reduced pressure for 24 hours or more in a vacuum dryer heated to 40°C. The weight measurement after this was taken as the dry weight. The wet weight and dry weight of the biocomponent adsorbent material 16 were used with Equation 1, and the obtained value was rounded off to the nearest whole number to calculate the water content of the water-insoluble material contained in the biocomponent adsorbent material 16. The water contents of the water-insoluble materials contained in the biocomponent adsorbent materials 17 to 19 were also measured in the same manner. The results are shown in Table 1.

[0126] <Measurement of sulfonic acid group content of water-insoluble materials contained in biocomponent adsorption materials 16-19> Except for using about 2 g of the biocomponent adsorbing material instead of about 1 g, the contents of sulfonic acid groups in the water-insoluble material contained in biocomponent adsorbing materials 16 to 19 were calculated in the same manner as in measuring the content of sulfonic acid groups in the water-insoluble material contained in biocomponent adsorbing material 1. The results are shown in Table 1.

[0127] 3.Performance evaluation The performance of biocomponent-adsorbing materials 1 to 14 and 16 to 20 was evaluated.

[0128] Comparative Example 1 For the biological component-adsorbing material 1, the interleukin 6 (IL-6) adsorption rate, heparin adsorption rate, and amount of eluate (eluate absorbance) were measured as follows.

[0129] <Measurement of IL-6 adsorption rate of biocomponent adsorption material 1> To confirm the IL-6 adsorption ability of the biocomponent-adsorbing material 1, the biocomponent-adsorbing material 1 was immersed in a liquid containing IL-6 for a predetermined period of time, then removed, and the IL-6 adsorption rate was measured from the difference in the amount of IL-6 in the liquid before and after the impregnation. The measurement method is as follows.

[0130] The biocomponent-adsorbing material 1 was cut into disks with a diameter of 6 mm, and four of the cut disks were placed in a polypropylene container. 30 mL of FBS, which had been adjusted to an IL-6 concentration of 10,000 pg / mL, was poured into the container at a depth of 1 cm. 3 The biocomponent adsorption material 1 was added to the biocomponent adsorption material 1, and the mixture was mixed by inversion for 2 hours in a 37°C incubator, after which the IL-6 concentration in the FBS was measured by ELISA. The IL-6 concentration was derived from the absorbance of the FBS before and after mixing by inversion. A microplate reader (Spectra Max M5, manufactured by Moleculara Devices) was used to measure the absorbance, with a measurement wavelength of 450 nm and a control wavelength of 595 nm, and a blank measurement without the biocomponent adsorption material was performed beforehand. The IL-6 adsorption rate was calculated from the IL-6 concentrations before and after mixing by inversion using the following formula 4. The results are shown in Table 2. IL-6 adsorption rate [%] = 100 × {IL-6 concentration before mixing [pg / mL] - IL-6 concentration after mixing [pg / mL]} / IL-6 concentration before mixing [pg / m] ··· Equation 4

[0131] <Measurement of heparin adsorption rate of biocomponent adsorption material 1> To confirm the heparin adsorption ability of the biocomponent-adsorbing material 1, the biocomponent-adsorbing material 1 was immersed in a physiological saline solution containing heparin for a predetermined period of time, then removed, and the heparin adsorption rate was measured from the difference in the amount of heparin in the liquid before and after the impregnation. The measurement method is as follows.

[0132] The biocomponent adsorption material 1 was cut into disks with a diameter of 6 mm, and the eight cut pieces were placed in a polypropylene container. 1.0 mL of physiological saline solution prepared so that the heparin concentration was 1.0 IU / mL was added to the eight 6 mm-diameter disks of the biocomponent adsorption material, and the container was mixed by inversion for 2 hours in an incubator at 37°C. The supernatant was collected and the absorbance at 210 nm was measured. Sodium heparin was used as the heparin. The same operation was performed on a blank without a biocomponent adsorption material. A solution with a heparin concentration of 10 IU / mL was serially diluted two-fold with physiological saline, and the absorbance at 240 nm was measured for each solution up to 0.078 IU / mL using an ultraviolet-visible absorption spectrophotometer (Shimadzu Corporation, UV-1280) to create a calibration curve. The 240 nm absorbance of the biocomponent-adsorbing material 1 and the blank were regression-tested against the calibration curve to calculate the heparin concentration, and the value obtained using the following formula 5 was rounded off to one decimal place to obtain the heparin adsorption rate. The results are shown in Table 2. Heparin adsorption rate [%] = {1.0 - (heparin concentration in the supernatant impregnated with biocomponent-adsorbing material 1 [IU / mL] / heparin concentration in the blank sample [IU / mL])} × 100 ··· Equation 5

[0133] <Measurement of the amount of eluted material from biocomponent adsorption material 1> In order to confirm the amount of elution from the biocomponent-adsorbing material 1, the biocomponent-adsorbing material 1 was immersed in distilled water for a predetermined time, then removed, and the absorbance of the supernatant after the immersion was measured. The measurement method is described below.

[0134] The biocomponent adsorption material 1 is placed on a sheet with an area of ​​6 cm 2The biocomponent adsorption material 1 was taken out and placed in a 50 mL centrifuge tube. 20 mL of Otsuka distilled water (Otsuka Pharmaceutical Factory) was added and the mixture was mixed by inversion for 5 minutes to wash. Only the water after washing was removed by decantation, and 20 mL of Otsuka distilled water (Otsuka Pharmaceutical Factory) was added again and mixed by inversion for 5 minutes. The biocomponent adsorption material 1 was taken out and added to a 6 mL glass vial (screw cap, lid with fluororesin packing). 1 mL of high performance liquid chromatograph distilled water (Fujifilm Wako Pure Chemical Industries, Ltd.) was added thereto, and the screw cap lid was closed to seal the material. The glass vial was placed in an incubator heated to 70°C and eluted for 24 hours. The supernatant solution after elution was taken out and the absorbance at 220 nm was measured at room temperature using an ultraviolet-visible absorption spectrophotometer (Shimadzu Corporation, UV-1280), and the value at this time was taken as the absorbance of the eluate. Before measuring the absorbance, only distilled water for high performance liquid chromatography was placed in a glass vial, and the solution left to elute for 24 hours was measured as a blank, and the background peak was subtracted. The results are shown in Table 2.

[0135] Comparative Example 2 Except for changing biocomponent-adsorbing material 1 to biocomponent-adsorbing material 2, measurements were performed in the same manner as in Comparative Example 1 to obtain the IL-6 adsorption rate, heparin adsorption rate, and eluate absorbance of biocomponent-adsorbing material 2. The results are shown in Table 2.

[0136] Example 1 Except for changing biocomponent-adsorbing material 1 to biocomponent-adsorbing material 3, measurements were performed in the same manner as in Comparative Example 1 to obtain the IL-6 adsorption rate, heparin adsorption rate and eluate absorbance of biocomponent-adsorbing material 3. The results are shown in Table 2.

[0137] Example 2 Measurements were carried out in the same manner as in Comparative Example 1, except that biocomponent-adsorbing material 1 was changed to biocomponent-adsorbing material 4, to obtain the IL-6 adsorption rate, heparin adsorption rate, and eluate absorbance of biocomponent-adsorbing material 4. The results are shown in Table 2.

[0138] Example 3 Measurements were carried out in the same manner as in Comparative Example 1, except that biocomponent-adsorbing material 5 was used instead of biocomponent-adsorbing material 1, to obtain the IL-6 adsorption rate, heparin adsorption rate, and eluate absorbance of biocomponent-adsorbing material 5. The results are shown in Table 2.

[0139] Example 4 Measurements were carried out in the same manner as in Comparative Example 1, except that biocomponent-adsorbing material 6 was used instead of biocomponent-adsorbing material 1, to obtain the IL-6 adsorption rate, heparin adsorption rate, and eluate absorbance of biocomponent-adsorbing material 6. The results are shown in Table 2.

[0140] Example 5 Except for changing biocomponent-adsorbing material 1 to biocomponent-adsorbing material 7, measurements were performed in the same manner as in Comparative Example 1 to obtain the IL-6 adsorption rate, heparin adsorption rate, and eluate absorbance of biocomponent-adsorbing material 7. The results are shown in Table 2.

[0141] Example 6 Except for changing biocomponent-adsorbing material 1 to biocomponent-adsorbing material 8, measurements were performed in the same manner as in Comparative Example 1 to obtain the IL-6 adsorption rate, heparin adsorption rate, and eluate absorbance of biocomponent-adsorbing material 8. The results are shown in Table 2.

[0142] Example 7 Except for changing biocomponent-adsorbing material 1 to biocomponent-adsorbing material 9, measurements were performed in the same manner as in Comparative Example 1 to obtain the IL-6 adsorption rate, heparin adsorption rate and eluate absorbance of biocomponent-adsorbing material 9. The results are shown in Table 2.

[0143] Example 8 Except for changing the biocomponent-adsorbing material 1 to the biocomponent-adsorbing material 10, the same procedures as in Comparative Example 1 were used to measure the IL-6 adsorption rate, heparin adsorption rate and eluate absorbance of the biocomponent-adsorbing material 10. The results are shown in Table 2.

[0144] Example 9 For the biological component-adsorbing material 17, the IL-6 adsorption rate, the heparin adsorption rate and the amount of eluate (eluate absorbance) were measured as follows.

[0145] <Measurement of IL-6 adsorption rate of biocomponent adsorbent material 17> The IL-6 adsorption rate of the biocomponent-adsorbing material 17 was measured in the same manner as in Comparative Example 1, except that instead of cutting the biocomponent-adsorbing material 1 into disks with a diameter of 6 mm and then placing four of the cut pieces in a polypropylene container, 0.05 mL of the biocomponent-adsorbing material 17 was sucked up with a pipette and placed in the polypropylene container. The results are shown in Table 2.

[0146] <Measurement of heparin adsorption rate of biocomponent adsorbent material 17> The heparin adsorption rate of the biocomponent adsorbing material 17 was measured in the same manner as in Comparative Example 1, except that instead of cutting the biocomponent adsorbing material 1 into disks with a diameter of 6 mm and then placing four of the cut pieces in a polypropylene container, 0.09 mL of the biocomponent adsorbing material 17 was sucked up with a pipette and placed in a polypropylene container. The results are shown in Table 2.

[0147] <Measurement of the amount of eluted material from biocomponent adsorption material 17> The biocomponent adsorption material 1 is placed on a sheet with an area of ​​6 cm 2 The same procedure as in Comparative Example 1 was used to measure the amount of eluted biocomponent-adsorbing material 17, except that 0.25 mL of biocomponent-adsorbing material 17 was sucked up with a pipette instead of cutting out the biocomponent-adsorbing material 17 so that the amount of eluted biocomponent-adsorbing material 17 was measured. The results are shown in Table 2.

[0148] Comparative Example 3 Except for changing the biocomponent-adsorbing material 1 to the biocomponent-adsorbing material 11, the same procedures as in Comparative Example 1 were used to measure the IL-6 adsorption rate, heparin adsorption rate and eluate absorbance of the biocomponent-adsorbing material 11. The results are shown in Table 2.

[0149] Comparative Example 4 Except for changing the biocomponent-adsorbing material 1 to the biocomponent-adsorbing material 12, the same procedures as in Comparative Example 1 were used to measure the IL-6 adsorption rate, heparin adsorption rate and eluate absorbance of the biocomponent-adsorbing material 12. The results are shown in Table 2.

[0150] Comparative Example 5 Except for changing the biocomponent-adsorbing material 1 to the biocomponent-adsorbing material 13, the same procedures as in Comparative Example 1 were used to measure the IL-6 adsorption rate, heparin adsorption rate and eluate absorbance of the biocomponent-adsorbing material 13. The results are shown in Table 2.

[0151] Comparative Example 6 Except for changing the biocomponent-adsorbing material 1 to the biocomponent-adsorbing material 14, the same procedures as in Comparative Example 1 were used to measure the IL-6 adsorption rate, heparin adsorption rate and eluate absorbance of the biocomponent-adsorbing material 14. The results are shown in Table 2.

[0152] Comparative Example 7 Except for changing the biocomponent-adsorbing material 17 to the biocomponent-adsorbing material 16, the same procedures as in Example 9 were carried out to obtain the IL-6 adsorption rate, heparin adsorption rate and eluate absorbance of the biocomponent-adsorbing material 16. The results are shown in Table 2.

[0153] Comparative Example 8 Except for changing biocomponent-adsorbing material 17 to biocomponent-adsorbing material 18, measurements were performed in the same manner as in Example 9 to obtain the IL-6 adsorption rate, heparin adsorption rate, and eluate absorbance of biocomponent-adsorbing material 18. The results are shown in Table 2.

[0154] Comparative Example 9 Measurements were carried out in the same manner as in Example 9, except that biocomponent-adsorbing material 17 was replaced with biocomponent-adsorbing material 19, to obtain the IL-6 adsorption rate, heparin adsorption rate, and eluate absorbance of biocomponent-adsorbing material 19. The results are shown in Table 2.

[0155] Comparative Example 10 Measurements were performed in the same manner as in Comparative Example 1, except that the biocomponent-adsorbing material 1 was changed to the biocomponent-adsorbing material 20, to obtain the IL-6 adsorption rate, heparin adsorption rate, and eluate absorbance of the biocomponent-adsorbing material 20. The results are shown in Table 2.

[0156] [Table 1]

[0157] The "Crosslinker name" in Table 1 refers to the name of the crosslinker used in preparing the biocomponent-adsorbing material. The results for biocomponent-adsorbing material 15 showed that when the biocomponent-adsorbing material is in a fibrous form, the biocomponent-adsorbing material will dissolve due to the introduction of sulfonic acid groups if a crosslinker is not used.

[0158] [Table 2]

[0159] The results of Comparative Examples 5, 6, and 9 in Table 2 show that the conventional biocomponent adsorbing materials (materials disclosed in Patent Documents 1, 2, and 3) have a lower IL-6 adsorption rate than the heparin adsorption rate, and there is a concern that competitive adsorption may occur. In contrast, the results of Comparative Examples 1 and 2 and Examples 1 and 3 show that the IL-6 adsorption rate can be increased while the heparin adsorption rate can be reduced by increasing the water content. In addition, the results of Examples 2, 3, and 4 and Comparative Examples 4 and 8 show that the IL-6 adsorption rate decreases whether the content of sulfonic acid groups is small or large. In addition, the results of Examples 5, 6, and 7 show that a high IL-6 adsorption rate and a low heparin adsorption rate are exhibited regardless of the origin of the crosslinked structure. In addition, the results of Example 9 show that even when the biocomponent adsorbing material is in a particulate form, a high IL-6 adsorption rate and a low heparin adsorption rate are exhibited. In addition, the results of Comparative Example 7 show that a particulate biocomponent adsorbing material generates eluates and has a low IL-6 adsorption rate if there is no crosslinked structure. Moreover, the results of Comparative Example 10 showed that the biocomponent-adsorbing material including a substrate containing a polymer having no aromatic ring in the repeating unit did not exhibit biocomponent adsorption performance. [Industrial Applicability]

[0160] The biological component adsorption material of the present invention can be used as an adsorption material in a biological component adsorption column intended for separating unwanted biological components, particularly in a biological component adsorption column for treating inflammatory diseases.

Claims

1. A water-insoluble material is provided, the water-insoluble material being composed of a substrate containing a polymer having an aromatic ring in a repeating unit, a sulfonic acid group immobilized on the substrate, and a crosslinked structure that crosslinks the polymers to each other, the content of the sulfonic acid group is 0.2 to 2.0 mmol per 1 g of the water-insoluble material; The water content of the water-insoluble material is 60% or more and less than 100%.

2. 2. The biocomponent-adsorbing material according to claim 1, wherein the water content is 60 to 95%.

3. 3. The biocomponent-adsorbing material according to claim 1, wherein the polymer is polystyrene or a polystyrene derivative.

4. The biocomponent-adsorbing material according to claim 1 or 2, wherein the maximum crosslinking rate of the polymer is greater than 0 and not greater than 1.00 mol %.

5. The biocomponent-adsorbing material according to claim 1 or 2, wherein the crosslinked structure is derived from formaldehyde or a substituted benzaldehyde.

6. A biological component adsorption column comprising the biological component adsorption material according to claim 1 or 2.

Citation Information

Patent Citations

  • Method for promoting drying of ink

    JP1984029197A

  • Blood component adsorption column

    JP2018102659A

  • Adsorbent for tumor necrosis factor-α, method for adsorption removal, and adsorber

    JP3633978B2

  • Fiber for protein adsorption and column for protein adsorption

    WO2016043223A1